(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2023)
For optimal safety of human health and their performance in ensuring higher productivity, certain constituents needs to be adequately harnessed together. Some of these are the quality of air, humidity and temperature, which serve as metrics, which guarantees quality life style. For this purpose, this paper becomes cardinal as it explains the significance of having a quality indoor air with the perfect humidity and temperature as predictors for fostering an atmosphere that enhances human health and productivity. This paper is underpinned by endogenous growth theory, whose principle posited that human productivity is a function of industrial development, since productivity of human reflects their capacity and output ratio. Thus, irrespective of how human productivity is being determined temperatures, humidity and indoor air quality plays dominant roles in enhancing human health and productivity. This paper concluded that for productivity to be increased, the quality of indoor air, humidity and temperature are metrics that must be continuously maintained; any lacunae left unturned in this regard can hamper productivity and consequently have negative results on human health.